Integer multiplication algorithm with delayed carry mechanism for public key cryptosystems - KOVTUN, Vladyslav Yu.; OKHRIMENKO, Andrew O. (Ukrainian Scientific Journal of Information Security, 2013)
Authors have offered the approach to increase performance of software implementation of integer multiplication algorithm, for 32-bit and 64-bit platforms. The approach relies on delayed carry mechanism of significant bit in sum accumulation. This strategy allows preventing necessity to consider the significant bit carry at the each iteration of the sum accumulation loop. The delayed carry mechanism enables to reduce the total number of additions and apply the modern parallelization technologies effectively.